"Beating against the Wind": The Politics of Race and Retention in Supporting African American Principal Advocacy and Growth. Issue 6 (November 2017) - Wilkerson, Reginald D.; Wilson, Camille M.
In this article, authors offer a CRT-driven analysis of in-depth interview data from two African American principals charged with turning around poverty-impacted, largely African-American populated schools. Both served as social justice-oriented leaders who countered traditional administrative approaches and disrupted racially and/or socioeconomically biased practices. Their leadership and student advocacy methods clashed with district ideals and policies, and each faced severe repercussions. The authors highlight why supporting and retaining such school leaders is necessary, and offer strategies capable of helping the educational community move forward in supporting a vulnerable leadership population commonly assigned to improve the most challenging U.S. schools.